Chest computed tomography scan findings of coronavirus disease 2019 (COVID-19) patients: a comprehensive systematic review and meta-analysis - Karimian, Mohammad (Pol J Radiol, 2021)
INTRODUCTION: Numerous cases of pneumonia caused by coronavirus disease 2019 (COVID-19) were reported in Wuhan, China. Chest computed tomography (CT) scan is highly important in the diagnosis and follow-up of lung disease treatment. The present meta-analysis was performed to evaluate chest CT scan findings in COVID-19 patients. MATERIAL AND METHODS: All research steps were taken according to the Meta-Analysis of Observational Studies In Epidemiology (MOOSE) protocol and the final report was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We registered this review at the International Prospective Register of Systematic Reviews (PROSPERO, CRD42019127858). RESULTS: Forty eligible studies including 4598 patients with COVID-19 were used for meta-analysis. The rate of positive chest CT scan in patients with COVID-19 was 94.5% (95% CI: 91.7-96.3). Bilateral lung involvement, pure ground-glass opacity (GGO), mixed (GGO pulse consolidation or reticular), consolidation, reticular, and presence of nodule findings in chest CT scan of COVID-19 pneumonia patients were respectively estimated to be 79.1% (95% CI: 70.8-85.5), 64.9% (95% CI: 54.1-74.4), 49.2% (95% CI: 35.7-62.8), 30.3% (95% CI: 19.6-43.6), 17.0% (95% CI: 3.9-50.9) and 16.6% (95% CI: 13.6-20.2). The distribution of lung lesions in patients with COVID-19 pneumonia was peripheral (70.0% [95% CI: 57.8-79.9]), central (3.9% [95% CI: 1.4-10.6]), and peripheral and central (31.1% [95% CI: 19.5-45.8]). The pulmonary lobes most commonly involved were the right lower lobe (86.5% [95% CI:57.7-96.8]) and left lower lobe (81.0% [95% CI: 50.5-94.7]). CONCLUSIONS: The most important outcomes in chest CT scan of patients with COVID-19 pneumonia were bilateral lung involvement, GGO or mixed (GGO pulse consolidation or reticular) patterns, thickened interlobular septa, vascular enlargement, air bronchogram sign, peripheral distribution, and left and right lower lobes involvement. Our study showed that chest CT scan has high sensitivity in the diagnosis of COVID-19, and may therefore serve as a standard method for diagnosis of COVID-19.